2017
DOI: 10.1038/ajg.2016.530
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intragastric Balloons on Obesity-Related Co-Morbidities: A Systematic Review and Meta-Analysis

Abstract: ObjectivesTherapies less invasive than surgery and more effective than lifestyle and pharmacotherapy are needed to contend with the obesity epidemic. Intragastric balloons (IGBs) are a minimally invasive endoscopic weight loss method recently approved for use in the US. The purpose of the study is to assess the effect of IGBs on metabolic outcomes associated with obesity.MethodsMEDLINE, Embase, and Cochrane Database were searched through July 2016. Dual extraction and quality assessment of studies using Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 61 publications
0
41
0
2
Order By: Relevance
“…Specifically, Popov et al conducted a meta-analysis of 40 studies with 5,668 patients who underwent IGB placement. 14 The study showed significant improvement in SBP by 9.1 mm Hg, DBP by 4.6 mm Hg, TG by 33.4 mg/dL, HbA1c by 0.6%, AST by 3 U/L, and ALT by 9 U/L at the time of IGB removal at 6 months, when data from observational studies were pooled. 14 More recently, Jirapinyo et al conducted a meta-analysis on 14 studies with 412 patients with obesity and concomitant T2DM who underwent DJBL.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, Popov et al conducted a meta-analysis of 40 studies with 5,668 patients who underwent IGB placement. 14 The study showed significant improvement in SBP by 9.1 mm Hg, DBP by 4.6 mm Hg, TG by 33.4 mg/dL, HbA1c by 0.6%, AST by 3 U/L, and ALT by 9 U/L at the time of IGB removal at 6 months, when data from observational studies were pooled. 14 More recently, Jirapinyo et al conducted a meta-analysis on 14 studies with 412 patients with obesity and concomitant T2DM who underwent DJBL.…”
Section: Discussionmentioning
confidence: 85%
“…Intragastric balloon placement allows for earlier interventions in obese patients who are not candidates for surgery and serves as a bridge to surgery in the morbidly obese . In addition, IGBs have proven useful in improving HbA1c, blood pressure, and weight circumference in those with metabolic syndrome …”
Section: Space‐occupying Therapiesmentioning
confidence: 99%
“…5 In addition, IGBs have proven useful in improving HbA1c, blood pressure, and weight circumference in those with metabolic syndrome. 5,7 Currently, three IGB systems have been FDA approved for weight loss and are commercially available in the US: the Orbera Intragastric Balloon System (Apollo Endosurgery, Austin, Texas), the ReShape Integrated Dual Balloon System (ReShape Medical, San Clemente, California), and the Obalon Balloon System (Obalon Therapeutics, Carlsbad, California).…”
Section: Space-occupying Therapiesmentioning
confidence: 99%
“…In einer Metaanalyse von 9 Studien mit insgesamt 267 Patienten betrug die mittlere Differenz des BMI − 3,4 (95 %-KI − 3,5 -− 3,24; p < 0,05) und der mittlere EWL 11,25 % (95 %-KI 10,61-11,89; p < 0,05) [12].…”
Section: Bridging-verfahrenunclassified
“…Der Einsatz von wassergefüllten Ballonsystemen zeigt hinsichtlich der Gewichtsreduktion deutlich bessere Ergebnisse [12,13]. Daten zum optimalen Zeitpunkt der Ballonexplantation 3 vs. 6 Monate existieren in der Literatur nicht.…”
Section: Bridging-verfahrenunclassified